Strategic agility and the role of HR as a strategic business partner: An Indian perspective - Ananthram, Subramaniam; Nankervis, Alan (John Wiley & Sons Ltd., 2013)
Competitive advantage has become the primary imperative for firms operating in an increasingly dynamic global marketplace, and may best be viewed through the dual prisms of strategic management and strategic human resource management (SHRM) theories. The adoption of a strategic business partner role by human resources (HR) has considerable potential to contribute to the strategic agility that firms require to successfully compete globally. This paper reports on a qualitative study of senior Indian managers' perspectives of these issues. It reinforces the importance of strategic agility, the need for close alignment between business and HRM strategies, and the growing emergence of a strategic business partner role for HR professionals in the Indian context. These findings have implications for researchers, senior managers and their HR specialists.